(Supra)Molecular Switches Controlled by Artificial Signaling Cascades - Venkatesh, Jayashree; Sharma, Akanksha; De, Soumen; Pramanik, Susnata; Schmittel, Michael (Synlett, 2025)
Biological communication is an indispensable component of intra- and extracellular regulation of life. Inspired by such complicated control networks, systems chemistry has begun to advance tools for autonomous networks by developing communication protocols between molecular entities to up- and downregulate functions (simple catalysis, dual catalysis, time-encoded emission). However, up to now these protocols remain relatively simple, indicating that there will be a long way to self-sustaining and autonomous functional systems. This review focuses on communication in artificial multicomponent systems that operate under either equilibrium or dissipative conditions, detailing the design principles for their operations. Finally, we discuss the key differences between biological and artificial signaling, emphasizing the limitations of artificial signaling and suggesting future directions in the field of artificial signal transduction. 1 Introduction2 Communication and Information Processing in Artificial Systems: Toward Smart Systems Chemistry2.1 Type 1: External Signal with One Sender, One Messenger, and One Receiver2.2 Type 2: External Signal with One Sender, One Messenger, and Two Receivers2.3 Type 3: One/Two External Signal(s) with Two Senders, Two Messengers, and One/Two Receiver(s)2.4 Type 4: External Signal with Cascaded Communication Across Multiple Receivers2.5 Type 5: Signaling Cascade Leading to Multiple Chemical Reactions2.6 Type 6: Signaling Cascade with Self-Regulation3 The Bigger Picture4 Conclusion and Outlook
Keywords: supramolecular chemistry; organocatalysis; transition metal catalysis; host-guest systems; complexes; cascaded transformations; switch; receptors